PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWAPADA MATA PELAJARAN BAHASA ARAB DI KELAS II MI AL HIDAYAH GUPPI KOTA CIREBON - Aceng Jaelani (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2016)
Medium of learning is one of the external factors that need to be considered by a teacher in order to obtain optimal student learning outcomes. With the use of media images in the learning process, the material is expected to be delivered to students in Arabic can be easily understood and students can easily memorize vocabulary in Arabic, which in turn can result yan learn the maximum. The process of learning Arabic at Al Hidayah GUPPI MI Cirebon in general has been an interaction between teachers and students that is based on the lesson plan, so the learning activities running properly. But sometimes the teacher is less effective and efficient use of instructional media, but it is often found students who are not paying attention in class. So that student learning outcomes is not maximized.The purpose of this research is 1) To know the use of media images in the learning process. 2) To determine student learning outcomes in subjects Arabic. 3) To know the influence of media images to the learning outcomes of students in the subjects of Arabic at Al Hidayah class II MI GUPPI Cirebon. The method used in this research is quantitative method. This quantitative research design using Pre-Experimental Design with her form that is one-group pretest-posttest design. The use of media images in class II MI Al Hidayah GUPPI Cirebon according to research results, including the excellent category with a percentage of 91% in may have been among the categories of 81% - 100%. Level learning outcomes of students of class II MI Al Hidayah GUPPI Cirebon city of 39 respondents in the category fairly with the average pretest score of 54.84, and a mean value of 75.90 rataposttest in both categories. The use of media images have a positive influence on student learning outcomes by 62% and 38% of student learning outcomes are influenced by other factors.Keywords: Media Images, Learning Outcomes, Arabic.